Impact of tung oil and sodium silicate-coated wood chips on the performance of cement-based thermal insulation composites - Agnė Kairytė; Sylwia Makowska; Saulius Vaitkus; Arūnas Kremensas; Sigitas Vėjelis; Giedrius Balčiūnas (Journal of Materials Research and Technology)
Cement-based thermal insulation composites that contain plant-based aggregates are characterized by their low compressive strength and water resistance. A significant challenge also involves achieving a solid interfacial adhesion between such aggregates and a cement matrix, which is needed in order to develop energy-efficient cement-based thermal insulation composites (TICs) for building envelopes. Sodium silicate (SS) solution is an economical raw material that has the potential for use in the cement hydration process. In addition, the availability of an Si–OH group allows it to be grafted onto the surface of wood chips (WCs), thereby acting as a coupling agent in a cement-based TICs. However, as a coating material, it has certain limitations, as it is prone to cracking and brittleness. In order to overcome these negative aspects, the synergistic effect of a WC coating containing SS and tung oil (TO) was investigated. The results of this study indicated that an SS/TO coating enabled the thermal conductivity to be lowered by 4% and 3% in the dry and wet states, respectively, and the bending strength to be raised by 16% for a TIC with lower amount of cement compared to a control TIC with higher amount. This suggests the possibility of reducing the amount of cement used in TIC production while achieving better performance of the resulting products. Cement-based TICs with SS/TO coatings and WC particles were characterized by increases of 94% and 75% in compressive strength and reductions of 40% and 22% in water absorption with lower and higher amounts of cement, respectively.